Karakteristik Endapan Cairan Rumen Sapi asal Rumah Potong Hewan sebagai Feed Supplement - Budiansyah, Agus; Resmi, Resmi; Nahrowi, Nahrowi; Wiryawan, Komang G; Suhartono, Maggy T; Widyastuti, Yantyati (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2011)
The aims of this experiment were to  identify and characterize of sediment product from cattle rumen liquor as a source of amino acids, minerals and vitamins. The sediment were obtained as pellets upon centrifugation of rumen liquor at 10,000 g for 10 minutes for collection of supernatant. The sediment were evaluated for amino acids, minerals and vitamins composition and chararacterized for the pH,  solubility of dry matter, specific density, bulk and compacted bulk densities and angle of response. Result of the experiment showed that sediment contained higher minerals:  Na, K and Fe compared with the commercial premix, but lower in B-vitamins and amino acids. The composition of mineral Na, K, and Fe from rumen liquor of local cattle was 13.47%, 7.73 % and 14.52 %,  while Na, K, and Fe from  rumen liquor of  imported cattle was 18.40%, 10.25%, and 14.52% respectively. The sediment had pH range from 10.01-10.03, the dry matter solubility  was 35.5% up to 39.1%. The sediment from imported cattle had higher specific density, bulk and compacted bulk densities and angle of response than that of local cattle. It is concluded that sediment from cattle rumen liquor contained high Na, K and Fe, low amino acids and B-vitamin, high pH and low solubility.